DO SUSTAINABILITY REPORTING AND FIRM SIZE DRIVE FIRM VALUE? PROFITABILITY’S ROLE - Yohanna Thresia Nainggolan; Putri Nanda Sari; Doddy Setiawan (Politeknik Negeri Ambon, 2026)
Introduction: This study aims to determine the influence of sustainability reports and company size on firm Value with profitability as a variable moderation in energy and mining companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. Based on 110 research populations, there are 29 companies that meet the criteria for determining research samples using the technique Purposive sampling. Methods: Data analysis technique using linear regression analysis multiple regression and Moderated Regression Analysis (MRA) with research methods quantitative.Results: The research results showed that sustainability reports had an effect on firm Value, company size does not affect the value companies, profitability is not able to moderate the influence of sustainability reports on firm Value, and profitability is not able to moderate the influence company size to firm Value.Conclusion and suggestion : The study concludes that sustainability reports have a significant effect on firm value. However, firm size does not influence firm value, and profitability does not moderate the effect of sustainability reports or firm size on firm value. Investors should not base investment decisions solely on firm size and profitability, but should also consider the transparency of sustainability disclosures, as these provide relevant non-financial insights for evaluating long-term investment prospects. Keywords: Company Size, Firm Value, Sustainability Report